The Relationship Between Self-Control and Internet Addiction Among Students: A Meta-Analysis - Li, Shiqi; Ren, Ping; Chiu, Ming Ming; Wang, Chenxin; Lei, Hao (Frontiers in Psychology, 2021)
As past studies of self-control and Internet addiction showed mixed results, this meta-analysis of 83 primary studies with 80,681 participants determined whether (a) these students with less self-control had greater Internet addiction, and (b) age, culture, gender, Internet addiction measures, or year moderated these relations. We used a random-effects meta-analysis of Pearson product-moment coefficients r with Fisher’s z-transformation and tested for moderation with the homogeneity tests. The results showed a positive link between impulsivity and Internet addiction (r = 0.371, 95% CI = [0.311, 0.427]) and a negative link between restraint and Internet addiction (r = −0.362, 95% CI = [−0.414, −0.307]). The moderation analysis indicated that the correlation between impulsivity indicators and greater Internet addiction was stronger among undergraduates (18–22 years old) than among adolescents (10–17 years old). Furthermore, the negative link between a restraint indicator and Internet addiction was greater (a) among students in East Asia than those in Western Europe/North America, (b) among males than females and (c) when using the Internet addiction measures GPIUS or IAT rather than CIAS. Hence, these results indicate a negative link between self-control and Internet addiction, and this link is moderated by age, culture, gender, and Internet addiction measure.